Dynamic high-resolution spectroscopic frequency referencing for frequency sweeping interferometry. (25th April 2016) - Prellinger, Günther; Meiners-Hagen, Karl; Florian Pollinger,
Abstract: A spectroscopic reference for the intrinsic frequency calibration of a ranging system based on frequency-sweeping interferometry (FSI) is presented. Saturation spectroscopy of iodine transitions at 636.8 nm is used to generate well-defined frequency markers. The experimental and analytic implementation is shown to enable in principle a frequency determination with an uncertainty of 0.17 MHz for a coverage factor k  = 1. This corresponds to a relative standard uncertainty of 1.5 × 10 − 7 as contribution to the combined measurement uncertainty of the FSI-based length measurement. But the analysis also reveals the high sensitivity of the actually achievable measurement uncertainty to the quality of the spectroscopic reference data.